Macroscopic and Microscopic findings in a set of congenital anomalies in two calves produced through in Vitro production - Arenales Torres, Alexandre A. [UNESP]; Lima Lhamas, Cinthia [UNESP]; Macoris, Delphim da Graça [UNESP]; Vasconcelos, Rosemeri de Oliveira [UNESP] (My University, 2013)
In vitro production and somatic cell nuclear transfer are biotechnologies widely used for breeding cattle, although may result in congenital anomalies. This paper aims to report a set of congenital anomalies in two Nelore calves, a male and a female, produced through in vitro fertilization. The major anomalies revealed at necropsy were hypospadias, bifid scrotum, atresia ani and rectum ending in blind pouch in the male calf. In the female calf accessory spleen, atresia ani, underdevelopment of extern genitalia and urethral orifice, and rectum ending in blind pouch forming a uterus-rectum fistula were observed.
Keywords: Accessory spleen; Atresia ani; Bovine; Congenital anomalies; Hypospadias; In vitro production